A 10-year follow-up study of pulmonary function in symptomatic elite cross-country skiers athletes and bronchial dysfunctions - Verges, S.; Flore, P.; Rousseaux-Blanchi, M. P.; Wuyam, B. (Scandinavian Journal of Medicine & Science in Sports, 2004)
A high prevalence of asthma-like symptoms and abnormal bronchial reactivity to various stimuli has been reported among endurance athletes. This report presents the cases of three cross-country skiers who have shown a progressive development of airway obstruction during their sport careers. The observed decline in FEV1, FEV1/FVC and/or FVC (FEV, forced expiratory volume; FVC, forced expiratory vital capacity) was greater than expected from longitudinal regression equations describing the ageing effect on pulmonary function. The three subjects encountered abnormal respiratory discomfort during their sport activity which was not systematically associated with abnormal bronchial reactivity (either to methacholine or exercise hyperventilation). At the end of the follow-up periods (912 years), all three skiers presented objective signs of airflow limitations during intense exercise. This report suggests that repeated chronic hyperventilation of cold dry air in cross-country skiers for several years can induce permanent bronchial disorders which may include remodeling processes and induce ventilatory limitations during intense exercise.